2004
DOI: 10.1002/ijc.20632
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk associated with estrogen receptor expression in epithelial hyperplasia lacking atypia and adjacent lobular units

Abstract: Estrogen is associated with many epidemiologic risk factors for invasive breast cancer. Cells that express estrogen receptors (ERs) in epithelial hyperplasia lacking atypia (EHLA) may influence breast cancer progression. We conducted a nested case-control study of 268 women with biopsy-confirmed EHLA to determine whether immunohistochemical expression of ER␣ in EHLA affects subsequent breast cancer risk. Study subjects could not have a prior or current history of breast cancer or atypical hyperplasia. Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…6,9,10 Entry biopsies were performed between 1965 and 1982. The authors reviewed the available histologic slides from 54 women (70%), and for the remaining 23 women, information was obtained from pathology reports (n ¼ 13), subject interviews or medical records (n ¼ 8), and death certificates (n ¼ 2).…”
Section: Methodsmentioning
confidence: 99%
“…6,9,10 Entry biopsies were performed between 1965 and 1982. The authors reviewed the available histologic slides from 54 women (70%), and for the remaining 23 women, information was obtained from pathology reports (n ¼ 13), subject interviews or medical records (n ¼ 8), and death certificates (n ¼ 2).…”
Section: Methodsmentioning
confidence: 99%
“…In a nested case–control study, it has recently been demonstrated that patients with increased numbers of epithelial cells expressing estrogen receptor alpha (ERα) in normal lobular units are at increased risk of subsequent invasive breast cancer [11]. These results suggest that overexpression of estrogen receptor in benign breast epithelium may increase estrogen sensitivity, thereby creating a permissive state that can lead to malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…24 Recently, Gobbi et al designed a similar case-control study of HUT lesions in. 9 The authors analyzed their expression of ER-a manually in HUT foci from cases and control subjects and showed a higher risk of subsequently developing breast cancer in HUT patients with ER-a+ normal lobules (cutoff 10% for positivity). The authors, however, presented their data in the form of positive or negative expression and did not provide median values for the percentages of ER-a expression.…”
Section: Discussionmentioning
confidence: 99%